Stress corrosion cracking of copper in swollen bentonite simulating nuclear waste disposal environment. Issue 1 (21st October 2020) - Fujimoto, Shinji; Tsuchiya, Hiroaki; Ogawa, Soma; Iida, Yoshihisa; Taniguchi, Naoki
Abstract: Stress corrosion cracking (SCC) of pure copper in bentonite clay was examined using a slow strain rate test (SSRT). Bentonite was swollen with pure water or aqueous solutions containing NH3 of 5 and 10 mM. Thick corrosion films and particulate deposits were formed on the copper surface after the SSRT. Typical tarnish rupture‐type SCC occurred on pure copper in swollen bentonite with and without NH3 . The crack propagation rate was enhanced by NH3 . It is confirmed that a thick oxide layer was formed on copper during plastic deformation, resulting in tarnish crack‐type SCC. Many particulate deposits observed on the surface were formed due to the rapid dissolution of Cu 2+ ions to form porous CuO at local deformed sites, regardless of the SCC occurrence. Abstract : Stress corrosion cracking (SCC) of pure copper in bentonite clay was examined using a slow strain rate test (SSRT). Bentonite was swollen with pure water or aqueous solutions containing NH3 . Thick corrosion films and particulate deposits were formed on the copper surface after the SSRT. Typical tarnish rupture‐type SCC occurred on pure copper in swollen bentonite with and without NH3 . The crack propagation rate was enhanced by NH3 .